“I Made All Decisions Myself”: Breast Cancer Treatment Decision-Making by Receivers and Decliners - Eunjung Kim; Sou Hyun Jang; M Robyn Andersen; Leanna J Standish (Asia-Pacific Journal of Oncology Nursing, 2021)
Objective: Many women with breast cancer refuse adjuvant treatments. How they arrive at their respective decisions and whether they are passively or actively involved in making decisions is less known. We explored the different decision-making behaviors of women who received treatments (receivers) after being diagnosed with breast cancer and those who refused (decliners). Methods: Seven women (four receivers and three decliners) were recruited from the Breast Cancer Integrative Oncology Study. We conducted an inductive content analysis based on in-depth semi-structured interviews with open-ended questions. Results: Receivers reported that doctors and family members influenced their decision-making. Decliners perceived their doctors as supportive of their decisions and reported that the experience of adjuvant therapy of family and friends, the results of Oncotest, and concerns about side effects influenced their decision-making. Receivers expressed discomfort about their decisions, relied on books, whereas decliners used various sources to find information. Both receivers and decliners believed that they had made the decisions themselves. However, receivers were somewhat negative about doctors' advice. Receivers also reported that, sometimes, the decision-making process was lacking and reported discomfort with the treatment process. Conclusions: Women with breast cancer need support in understanding the care they are prescribed and getting essential care.